2004
DOI: 10.1021/bi0362875
|View full text |Cite
|
Sign up to set email alerts
|

Synaptobrevin Transmembrane Domain DimerizationRevisited

Abstract: Synaptobrevin is a membrane-spanning soluble N-ethyl maleimid-sensitive factor (NSF) attachment protein receptor (SNARE) protein of synaptic vesicles that is essential for neurotransmitter release. Various lines of evidence indicate that it exists alternatively as a monomer, as a homodimer, as a heterodimer with synaptophysin, or as a ternary complex with other SNAREs at the various stages of the synaptic vesicle cycle. Homodimerization of synaptobrevin was previously shown by different authors to depend on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…angle of 38 degrees, with residues 99, 102, 103, 107, 110 and 111 at the dimer interface (Laage and Langosch, 1997;Laage et al, 2000;Fleming and Engelman, 2001a;Roy et al, 2004). Whereas biophysical studies on the structure of the TMD are largely confined to membrane-mimetic environments in vitro, our studies using BiFC in intact cells indicate that these residues are not sufficient to mediate TMD interactions, and are not crucial for VAMP2-mediated fusion activity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…angle of 38 degrees, with residues 99, 102, 103, 107, 110 and 111 at the dimer interface (Laage and Langosch, 1997;Laage et al, 2000;Fleming and Engelman, 2001a;Roy et al, 2004). Whereas biophysical studies on the structure of the TMD are largely confined to membrane-mimetic environments in vitro, our studies using BiFC in intact cells indicate that these residues are not sufficient to mediate TMD interactions, and are not crucial for VAMP2-mediated fusion activity.…”
Section: Discussionmentioning
confidence: 76%
“…For example, individual VAMP2 or syntaxin-1A molecules have been reported to form TMD-mediated homodimers and heterodimers in a sequence-specific manner (Laage and Langosch, 1997;Margittai et al, 1999;Laage et al, 2000;Fleming and Engelman, 2001a;Kroch and Fleming, 2006;Tong et al, 2009). However, the relative affinity of such interactions has been controversial (Bowen et al, 2002;Roy et al, 2004), and their in vivo relevance remains unclear, given that all studies have been performed in vitro in detergent solution or in liposomes. In addition, although the crucial importance of the TMD of SNAREs for membrane fusion events is recognised (Langosch et al, 2007), the precise structural and functional requirements for the TMD, especially in intact cells, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have shown that native SNARE complexes purified from brain, or SNARE complexes assembled from recombinant full-length SNAREs containing transmembrane domains, assemble into star-shaped particles mostly containing three or four bundles emanating from their center (Rickman et al, 2005). Such structure may be obtained when two dimers associate with each other through their transmembrane domains (Hohl et al, 1998;Laage et al, 2000;Bowen et al, 2002;Roy et al, 2004). Unfortunately, when only one of the two SNAREs carried a transmembrane domain, reassembly experiments led to the generation of large irregular aggregates (Rickman et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…SNAREs in membrane fusion and bilayer mixing SNAREs are anchored to membranes by transmembrane segments (TMSs) that not only anchor them, but also contribute to SNARE-SNARE interactions and appear to play an active role in the fusion process. The synaptic R-SNARE synaptobrevin II and the Q-SNARE syntaxin 1A homo-and heterodimerize in vitro through a conserved motif within their respective ␣-helical TMSs (Laage and Langosch, 1997; Margittai et al, 1999;Laage et al, 2000;Roy et al, 2004) that forms a tightly packed interface (Fleming and Engelman, 2001). The long axes of these transmembrane helices are proposed to cross each other at a negative angle; by contrast, the soluble helices of the cytoplasmic SNARE domains assume a positive packing angle upon formation of the coiled-coil structure of the assembled SNARE complex.…”
Section: Structure Of Snaresmentioning
confidence: 99%
“…In neurotransmitter release, only part of synaptobrevin complexes with Q-SNAREs on the vesicle (Kretzschmar et al, 1996). The rest appears either to associate with the synaptic vesicle protein synaptophysin or to homodimerize (Calakos and Scheller, 1994;Edelmann et al, 1995;Washbourne et al, 1995;Pennuto et al, 2002;Roy et al, 2004). At the plasma membrane, syntaxin and SNAP-25 seem to assemble in cis prior to trans complex formation with the R-SNARE (Pabst et al, 2002;An and Almers, 2004;Fasshauer and Margittai, 2004).…”
Section: Mechanism Of Membrane Fusion By Snares Snare Pairingmentioning
confidence: 99%